Biomass, chemical composition and digestibility of some vegetable and legume residues for ruminants in the Chaouia area - Sibaoueih M.; Hamidallah N.; Chriyaa A. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
This study was carried out to evaluate the biomass, chemical composition and in vitro dry matter digestibility (IVDMD) of some crop by-products. Two categories were evaluated. First group included vegetable residues such as cauliflower (CR), sweet potato (SPR), fennel (FR), vegetable beet (VBR), artichoke (AR), turnip (TR), carrot (CAR) and the second group included legume residues such as bean (BR), lentil (LR) and pea (PR). The total dry biomass was evaluated by the quadrat method at harvesting. It was approximately 100,000 tons of which 76% are legume residues. The dry matter (DM) varied between 13.5 % in VBR to 19.7 % in SPR while the average was about 95.1% for legume residues. The lowest crude protein (CP) content was recorded in PR showing 57.8 g / kg DM while the highest was from the VBR with 181 g / kg DM. The legume residues (BR, LR and PR) recorded higher neutral detergent fiber (NDF) values of 487, 472.8 and 500 g / kg DM, respectively. The average acid detergent fiber (ADF) content of vegetable and legume residues was 227 and 394 g / kg DM, respectively. Acid detergent lignine (ADL) ranged from 16.6 in CR to 108 g / kg DM in LR. Ash content of vegetable residues ranged from 118 in SPR to 279 g / kg DM in VBR and was on average 114 g / kg DM in legume residues. The TR recorded the highest IVDMD being 66 % followed by VBR 61.6 % with the lowest value obtained for SPR being 32.7 %. The biomass of different crops by-products is not negligible and could be used as part of the diet of ruminants according to their nutritive value.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)